FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN TURNOVER AKUNTAN WANITA - Festiari Nindaerrosa; Haryanto Haryanto (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to examine that role conflict, social comparison with peers, stress, gender discrimination, physical appearance, and age are associated with the turnover decision made by female accountant.  Multinominal logistic regression is used to analyze survey data from 90 female accountants from KAP Big Four, KAP non Big Four, and government sector (Biro Akuntansi Diponegoro University and BPKP in Indonesia) were selected by purposive sampling.  Social comparison theory used to explain the influence between variables. Variables were measured using likert scale 1-5. The result of this research show that only stress, gender discrimination, and physical appearance have significant positive effect on turnover decision female accountant associate with government sector.  Furthermore, associate with KAP non Big Four only role conflict.